2001
DOI: 10.1007/s002130100759
|View full text |Cite
|
Sign up to set email alerts
|

Effects of psychostimulant withdrawal on latent inhibition of conditioned active avoidance and prepulse inhibition of the acoustic startle response

Abstract: Rationale: Chronic intermittent administration of amphetamine and cocaine can precipitate psychotic episodes in humans and produce persistent behavioral changes (i.e. increased locomotion, stereotypy) in the rat. The psychostimulant sensitization model of psychosis holds that the repeated administration of drugs such as amphetamine and cocaine induces long-lasting neuroadaptations and behavioral outcomes in animals that parallel aspects of the schizophrenic condition. Objectives: In the present study, we attem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 68 publications
(83 reference statements)
5
11
0
Order By: Relevance
“…Manipulations of the PPI testing environment that were intended to simulate the experimental conditions considered optimal for demonstrating behavioral sensitization (contextual associations, presence of a DA agonist challenge, later withdrawal time points for testing) likewise did not reveal any increased sensitivity of AMPH-withdrawn animals to PPI disruption. Such a dissociation between LI and PPI has been shown previously following other behavioral and pharmacological treatments (Wilkinson et al 1994;Feldon et al 2000;Murphy et al 2001a). The existence of this dissociation may be due at least in part to the suggested involvement of different brain regions in the mediation of LI and PPI.…”
Section: Discussionsupporting
confidence: 73%
“…Manipulations of the PPI testing environment that were intended to simulate the experimental conditions considered optimal for demonstrating behavioral sensitization (contextual associations, presence of a DA agonist challenge, later withdrawal time points for testing) likewise did not reveal any increased sensitivity of AMPH-withdrawn animals to PPI disruption. Such a dissociation between LI and PPI has been shown previously following other behavioral and pharmacological treatments (Wilkinson et al 1994;Feldon et al 2000;Murphy et al 2001a). The existence of this dissociation may be due at least in part to the suggested involvement of different brain regions in the mediation of LI and PPI.…”
Section: Discussionsupporting
confidence: 73%
“…For example, although Druhan et al (1998) found a leftward shift in the Amp dose-response curve, there appeared to be little evidence of sensitization to a challenge dose of 0.5 mg/kg. Similarly, although the rats used by Murphy et al (2001a) showed enhanced responses to an Amp challenge of 1.5 mg/kg these effects were reported as being not statistically significant. These small effects are in contrast with the robust (250%) increase in Amp-stimulated activity observed with our rats.…”
Section: Discussionmentioning
confidence: 57%
“…A striking feature of these studies is the variety in methods used to induce sensitization particularly regarding the dose of Amp and the frequency of injections. Two of these studies used 1.5 mg/kg on five consecutive days (Murphy et al 2001a) and 2 mg/kg every 3 days for six injections (Druhan et al 1998). The strength of sensitization, as indexed by shifts in the magnitude of locomotor stimulant effects of a challenge dose of Amp, seem to differ across these various schedules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports also describe information processing deficits following sensitizing regimens of amphetamine. Rats with prior exposure to amphetamine show reduced prepulse inhibition (PPI) of the acoustic startle reflex (Tenn et al 2003) and disrupted latent inhibition (LI) (Murphy et al 2001), and exhibit a variety of deficits in tests of visual attention (Dalley et al 2005;Deller and Sarter 1998;Kondrad and Burk 2004). Thus, exposure to stimulants may also alter cognitive function.…”
Section: Introductionmentioning
confidence: 98%